2017
DOI: 10.3832/ifor1748-009
|View full text |Cite
|
Sign up to set email alerts
|

Sap flow, leaf-level gas exchange and spectral responses to drought in Pinus sylvestris, Pinus pinea and Pinus halepensis

Abstract: In a climate change scenario, Mediterranean forest species such as pines may be endangered by rising temperatures and reduced precipitation, thus calling for studies on the transpiration and water balance in pines. In this paper, the response of young plants of Pinus sylvestris L., Pinus pinea L. and Pinus halepensis Mill. to different irrigation treatments has been studied. Significant differences were found in water potential, sap flow, leaf-level gas exchange and spectral variables. P. sylvestris had higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…(T air − T leaf ) in crop systems (Rossini et al, 2013;Suarez et al, 2008). Our results agree with Marino et al (2014) who showed a linear relationship between sap flux density and leaf-level PRI in olive trees (R 2 = 0.42), and Manzanera et al (2017) who showed significant correlation between sap flow rate and single-tree PRI (R 2 = 0.62) in juvenile potted pines. We build upon these previous efforts by reporting for the first time, to our knowledge, a relationship between PRI and sap flow in a natural mature forest using novel canopy measurements of seasonal PRI at daily resolution.…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 89%
See 2 more Smart Citations
“…(T air − T leaf ) in crop systems (Rossini et al, 2013;Suarez et al, 2008). Our results agree with Marino et al (2014) who showed a linear relationship between sap flux density and leaf-level PRI in olive trees (R 2 = 0.42), and Manzanera et al (2017) who showed significant correlation between sap flow rate and single-tree PRI (R 2 = 0.62) in juvenile potted pines. We build upon these previous efforts by reporting for the first time, to our knowledge, a relationship between PRI and sap flow in a natural mature forest using novel canopy measurements of seasonal PRI at daily resolution.…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 89%
“…While a number of studies in crop systems have demonstrated the link between seasonal PRI and measures or proxies of plant hydraulics (Magney et al, 2016; Rossini et al, 2013; Sarlikioti et al, 2010; Suarez et al, 2008; Zarco‐Tejada et al, 2012), or shown that PRI is a good indicator of leaf water status (Ripullone et al, 2011; Sun et al, 2014), few have attempted to relate PRI to sap flow rates (Manzanera et al, 2017; Marino et al, 2014); although PRI has been shown to vary with a proxy for transpiration ( T air − T leaf ) in crop systems (Rossini et al, 2013; Suarez et al, 2008). Our results agree with Marino et al (2014) who showed a linear relationship between sap flux density and leaf‐level PRI in olive trees ( R 2 = 0.42), and Manzanera et al (2017) who showed significant correlation between sap flow rate and single‐tree PRI ( R 2 = 0.62) in juvenile potted pines. We build upon these previous efforts by reporting for the first time, to our knowledge, a relationship between PRI and sap flow in a natural mature forest using novel canopy measurements of seasonal PRI at daily resolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salazar-Tortosa et al, 2018). In this sense, the weaker stomatal control of P. halepensis and P. pinea (Manzanera et al, 2016) can help these species to maintain growth and tolerate dry periods better than P. nigra or P. sylvestris. Another potential explanation for the greater resilience capacity of P. halepensis and P. pinea can be found in their greater capacity to invest more in belowground organs in response to drought (Sarris and Mazza, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Stone pine is mostly distributed in coastal areas (Vendramin et al 2008), which are considered one of the best sites for growth (Bussotti 1997;Campelo et al 2007;Manzanera et al 2016); in the coasts of Italy and Spain, soils are alluvial, volcanic (Costantini et al 2004), or littoral dunes (Muñoz and Gracía 2009;Piraino et al 2012). However, Handling Editor: Barry A. Gardiner Contribution of the co-authors VL designed the study, directed the projects that funded the study, and wrote most of the paper.…”
Section: Introductionmentioning
confidence: 99%